Defective 2D silicon phosphide monolayers for the nitrogen reduction reaction: a DFT study. Issue 15 (30th March 2022) - Guo, Zhongyuan; Wang, Tianyi; Liu, Haikun; Qiu, Siyao; Zhang, Xiaoli; Xu, Yongjun; Langford, Steven J.; Sun, Chenghua
Abstract : 2D SiP with P-defects as a metal-free catalyst exhibits high activity and selectivity towards the electrochemical NRR. Abstract : Electroreduction of N2 is a highly promising route for NH3 production. The lack of efficient catalysts that can activate and then reduce N2 into NH3 limits this as a pragmatic application. In this work, a 2D layered group IV–V material, silicon phosphide (SiP), is evaluated as a suitable substrate for the electrochemical nitrogen reduction reaction (ENRR). To capture N2, one phosphorus (P) defect was introduced on the plane of SiP. DFT calculations found that the defective SiP monolayer (D1-SiP, which is defined by the P-defect on SiP) exhibits enormous prospects towards the ENRR because of enhanced electron conductivity, good activation on N2, lower limiting potential ( U L = −0.87 V) through the enzymatic pathway, smooth charge transfer between the catalyst and the reaction species, and robust thermal stability. Importantly, D1-SiP demonstrates the suppressed activities on producing of H2 and N2 H4 side-products. This research demonstrates the potential of 2D metal-free Si-based catalysts for nitrogen fixation and further enriches the study of group IV–V materials for the ENRR.